Batasan Wewenang Peradilan Agama DiIndonesia Dalam Penyelesaian Sengketa Ekonomi Syariah - Abdul Mughni; Muhammad Hanafi (Jurnal Hukum Ekonomi Syariah, 2019)
At 2006, a government has issued constitution No.3/2006 aboutreligious court.Which is an amandement of constitutions No.7/1989. Whereinconstitution No.3/2006, an authority of religious court has been expanded. Andinserting a dispute retolution of Islamic economic as a part of absolut authority ofreligious court, as described in clause No.49 constitution No.3/2006. The research hasapplied normatively, which using positive law principles in sync. Then compare it toknow the practice of that law in a reality. And the data was collected from literature(case) study, and reinforced by an interview. The findings is, the constitution cannotimplemented effectively in religious court. Because of an unstability of theregulations of Islamic economic in religious court.